Clinical Efficacy and In Vitro Drug Sensitivity Test Results of Azithromycin Combined With Other Antimicrobial Therapies in the Treatment of MDR P. aeruginosa Ventilator-Associated Pneumonia - Huang, Yuqin; Wang, Wenguo; Huang, Qiang; Wang, Zhengyan; Xu, Zhuanzhuan; Tu, Chaochao; Wan, Dongli; He, Miaobo; Yang, Xiaoyi; Xu, Huaqiang; Wang, Hanqin; Zhao, Ying; et al. (Frontiers in Pharmacology, 2022)
Objective: The aim of the research was to study the effect of azithromycin (AZM) in the treatment of MDR P. aeruginosa VAP combined with other antimicrobial therapies. Methods: The clinical outcomes were retrospectively collected and analyzed to elucidate the efficacy of different combinations involving azithromycin in the treatment of MDR-PA VAP. The minimal inhibitory concentration (MIC) of five drugs was measured by the agar dilution method against 27 isolates of MDR-PA, alone or in combination. Results: The incidence of VAP has increased approximately to 10.4% (961/9245) in 5 years and 18.4% (177/961) caused by P. aeruginosa ranking fourth. A total of 151 cases of MDR P. aeruginosa were included in the clinical retrospective study. Clinical efficacy results are as follows: meropenem + azithromycin (MEM + AZM) was 69.2% (9/13), cefoperazone/sulbactam + azithromycin (SCF + AZM) was 60% (6/10), and the combination of three drugs containing AZM was 69.2% (9/13). The curative effect of meropenem + amikacin (MEM + AMK) was better than that of the meropenem + levofloxacin (MEM + LEV) group, p = 0.029 (p < 0.05). The curative effect of cefoperazone/sulbactam + amikacin (SCF + AMK) was better than that of the cefoperazone/sulbactam + levofloxacin (SCF + LEV) group, p = 0.025 (p < 0.05). There was no significant difference between combinations of two or three drugs containing AZM, p > 0.05 (p = 0.806). From the MIC results, the AMK single drug was already very sensitive to the selected strains. When MEM or SCF was combined with AZM, the sensitivity of them to strains can be significantly increased. When combined with MEM and AZM, the MIC50 and MIC90 of MEM decreased to 1 and 2 ug/mL from 8 to 32 ug/mL. When combined with SCF + AZM, the MIC50 of SCF decreased to 16 ug/mL, and the curve shifted obviously. However, for the combination of SCF + LEV + AZM, MIC50 and MIC90 could not achieve substantive changes. From the FIC index results, the main actions of MEM + AZM were additive effects, accounting for 72%; for the combination of SCF + AZM, the additive effect was 40%. The combination of AMK or LEV with AZM mainly showed unrelated effects, and the combination of three drugs could not improve the positive correlation between LEV and AZM. Conclusion: AZM may increase the effect of MEM or SCF against MDR P. aeruginosa VAP. Based on MEM or SCF combined with AMK or AZM, we can achieve a good effect in the treatment of MDR P. aeruginosa VAP.